MAKING CHICKEN NUGGETS WITH THE ADDITION OF TEMPEH IN LAMBUNOT PAYA VILLAGE, KUTA BARO DISTRICT, ACEH BESAR REGENCY: PEMBUATAN NUGGET AYAM DENGAN PENAMBAHAN TEMPE DI DESA LAMBUNOT PAYA KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Irhami; Chairil Anwar; Ika Rezvani Aprita; Mulla Kemalawaty; Irmayanti (PT. ROCE WISDOM ACEH, 2024)
Lambunot Paya Village is a village that has a lot of land, such as rice fields and gardens, so some of the residents make their living as farmers and some as livestock breeders. The PkM activity carried out in Lambunot Paya Village is the activity of processing chicken meat into tempeh nugget products. The chicken nugget product with the addition of tempeh was chosen as a food diversification product because Lambunot Paya village has excellent potential regarding livestock commodities, one of which is chicken. So far, people have been selling livestock (chickens) in intact condition. This is done to increase the selling value of livestock commodities so that it can improve the economy of village communities. This activity is carried out by providing materials and training to the community regarding techniques for making nuggets with the addition of tempeh, the nutritional content of nuggets, and the safety level of nugget products. The results of the activities carried out were very good, this can be seen from the community's ability to process chicken into nugget products which have high nutritional value with the addition of tempeh. The community hopes that similar training activities can be carried out again periodically with different processed products.